Validation of the Social Media Disorder Scale in Adolescents: Findings From a Large-Scale Nationally Representative Sample. (December 2022) - Boer, Maartje; Stevens, Gonneke W. J. M.; Finkenauer, Catrin; Koning, Ina M.; van den Eijnden, Regina J. J. M.
Large-scale validation research on instruments measuring problematic social media use (SMU) is scarce. Using a nationally representative sample of 6, 626 Dutch adolescents aged 12 to 16 years, the present study examined the psychometric properties of the nine-item Social Media Disorder scale. The structural validity was solid, because one underlying factor was identified, with adequate factor loadings. The internal consistency was good, but the test information was most reliable at moderate to high scores on the scale's continuum. The factor structure was measurement invariant across different subpopulations. Three subgroups were identified, distinguished by low, medium, and high probabilities of endorsing the criteria. Higher levels of problematic SMU were associated with higher probabilities of mental, school, and sleep problems, confirming adequate criterion validity. Girls, lower educated adolescents, 15-year-olds, and non-Western adolescents were most likely to report problematic SMU. Given its good psychometric properties, the scale is suitable for research on problematic SMU among adolescents.